2020
DOI: 10.1371/journal.pone.0232968
|View full text |Cite
|
Sign up to set email alerts
|

Exploring psychosocial factors that influence smartphone dependency among Korean adolescents

Abstract: This study investigated the relationships among psychosocial factors that contribute to smartphone dependency among South Korean adolescents. This cross-sectional study involved the secondary data analysis of the 2016 Korean Children and Youth Panel Survey, a nationwide multistage cluster survey. Data were collected from 1,840 7th grade students in South Korea and analyzed with descriptive statistics, Pearson's correlation coefficients, and a path analysis using SPSS 21.0 and AMOS 23.0. The path analysis showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 20 publications
0
16
0
3
Order By: Relevance
“…In some cases, children are aware of the negative consequences correlated to media use. In fact, European children declared that MD may cause “lack of sleep, problems in doing homework and with study concentration” [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, children are aware of the negative consequences correlated to media use. In fact, European children declared that MD may cause “lack of sleep, problems in doing homework and with study concentration” [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, adolescents may have a low perception of the risks related to an excessive MD [ 10 ]. Few studies explored the perception of risk by adolescents and, among them, a European study reported that children are aware that MD may cause “lack of sleep, problem in doing homework and with study concentration” [ 11 , 12 ]. In this scenario, parents and caregivers have a crucial role in monitoring children and giving them the optimal behaviour for MD use [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent gender was used as a moderator. Adolescent depressive symptoms and self-esteem, which were found to be important factors of adolescent smartphone dependency in previous studies [4,29,40] were also controlled as covariates. Perceived economic status was coded as 0 = low, 1 = average, 2 = high.…”
Section: Covariatesmentioning
confidence: 99%
“…There is a widespread use of and access to smartphone and mobile devices, with mobile phone technology penetration at nearly 100% worldwide. South Korea has among the highest ownership percentages (94%) [ 4 ]. Their improved geolocation capacity and access to broadband and satellite communication infrastructure have enabled emergency alert SMS text messages to be sent to end users directly [ 5 ].…”
Section: Introductionmentioning
confidence: 99%